Oakleaf Bearers - John Flanagan (London : Corgi Yearling, 2008)
Evanlyn has been taken captive by a mysterious horseman. Will's attempts to rescue her lead him into the territory of a fearsome new enemy. Now, he must unite with old rivals to vanquish this greater threat. But can the fragile truce survive the battle?